NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIAEvolution of cardiovascular risk with advancing stages of chronic kidney disease - Rozentryt, Piotr; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Chronic kidney disease is one of the most important clinical problems of modern medicine. Its prevalence is high worldwide and it carries significant cardiovascular risk. Consequently, chronic kidney disease is associated with excessive cardiovascular morbidity and mortality. The staging of chronic kidney disease into 5 phases is based on the chronic presence of injury markers in the urine, of which the most important is microalbuminuria, and estimated glomerular filtration rate. The nature of this staging results in large variation of cardiovascular risk within the whole entity. The progressive character of chronic kidney diseases causes evolution of risk markers and cardiovascular hazard at each stage of the diseases. In the article the definition and epidemiology of chronic kidney disease are briefly described. The authors focus on evolutionary analysis of cardiovascular risk in the disease. They point out sources and character of cardiovascular risk at consecutive stages of chronic kidney disease, paying particular attention to changes of baseline risk factors caused by progress of the diseases. In the final paragraph the article shows amplification of overall risk within the whole natural history of chronic kidney disease.